2022
DOI: 10.1371/journal.pone.0268926
|View full text |Cite
|
Sign up to set email alerts
|

Key predictors of COVID-19 vaccine hesitancy in Malaysia: An integrated framework

Abstract: Background As the vaccination drive against the coronavirus disease (COVID-19) in Malaysia progresses rapidly, the main challenge will gradually shift from procuring and distributing vaccines to ensuring the broadest possible acceptance among all population segments. Therefore, this study used the integrated framework of the health belief model (HBM) and the theory of reasoned action (TRA) to investigate the predictors of intention to receive COVID-19 vaccines in Malaysia. Methodology A market research compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 27 publications
4
19
1
Order By: Relevance
“…Further, the Malaysian National Immunization Programme employed many other approaches and actions to promote vaccination, such as active negotiation with multiple vaccine supplier countries/companies for procurement, vaccine prioritization for at-risk people (front liners, those with chronic diseases, and the elderly), and care for the elderly and the vulnerable by providing special services and assistance for easy access to the vaccine. This could explain the relatively high level of vaccination and lower level of hesitancy among Malaysians, which is ascribed to positive attitudes and a high level of trust among them [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the Malaysian National Immunization Programme employed many other approaches and actions to promote vaccination, such as active negotiation with multiple vaccine supplier countries/companies for procurement, vaccine prioritization for at-risk people (front liners, those with chronic diseases, and the elderly), and care for the elderly and the vulnerable by providing special services and assistance for easy access to the vaccine. This could explain the relatively high level of vaccination and lower level of hesitancy among Malaysians, which is ascribed to positive attitudes and a high level of trust among them [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative analysis that explored the intention to receive or not receive COVID-19 vaccine among Malaysians using an integrated framework of theory of reasoned action and health belief model, it was found that the predictors of vaccine hesitancy were age, religious beliefs, subjective norms, susceptibility, attitude, and vaccine confidence or trust [24]. In contrast to the findings of a global survey from seventeen countries which reported increasing vaccine hesitancy with increase in age [7], this study reported that the vaccine hesitancy was higher among those young, primarily driven by perceived (low) risk of COVID-19.…”
Section: Covid-19 Vaccines -Current State and Perspectivesmentioning
confidence: 99%
“…In contrast to the findings of a global survey from seventeen countries which reported increasing vaccine hesitancy with increase in age [7], this study reported that the vaccine hesitancy was higher among those young, primarily driven by perceived (low) risk of COVID-19. The study also stressed the importance of social influence; an individual is more likely to get vaccinated if one or the other in his/her closest circle is either vaccinated or intend to get vaccinated [24].…”
Section: Covid-19 Vaccines -Current State and Perspectivesmentioning
confidence: 99%
“…In their study of the willingness of health care workers to take the COVID-19 vaccination, Kumar et al (2021) uncovered wide-ranging justifications for vaccine hesitance, including vaccine safety concerns, anti-vaccination persuasions, personal choice, and waiting until others took the vaccine. Religious belief and various forms of religiosity can shape people's attitudes toward their health and COVID-19 vaccines specifically (Aziz, Niazi, & Ghani 2022;Ng et al, 2022;Salam, 2021). Corcoran, Scheitle, and DiGregorio (2021) identify Christian nationalism as one of the leading predictors of COVID-19 vaccine hesitancy.…”
Section: Literature Review: Attitudes Toward Covid 19 Vaccinesmentioning
confidence: 99%